Voltage-dependent calcium channels are involved in neurogenic dural vasodilatation via a presynaptic transmitter release mechanism - Akerman, S (2003)
1. A missense mutation of the CACNA1A gene that encodes the α(1A) subunit of the voltage-dependent P/Q-type calcium channel has been discovered in patients suffering from familial hemiplegic migraine. This suggested that calcium channelopathies may be involved in migraine more broadly, and established the importance of genetic mechanisms in migraine. 2. Channelopathies share many clinical characteristics with migraine, and thus exploring calcium channel functions in the trigeminovascular system may give insights into migraine pathophysiology. It is also known that drugs blocking the P/Q- and N-type calcium channels have been successful in other animal models of trigeminovascular activation and head pain. 3. In the present study, we used intravital microscopy to examine the effects of specific calcium channel blockers on neurogenic dural vasodilatation and calcitonin gene-related peptide (CGRP)-induced dilation. 4. The L-type voltage-dependent calcium channel blocker calciseptine significantly attenuated (20 μg kg(−1), n=7) the dilation brought about by electrical stimulation, but did not effect CGRP-induced dural dilation. 5. The P/Q-type voltage-dependent calcium channel blocker ω-agatoxin-IVA (20 μg kg(−1), n=7) significantly attenuated the dilation brought about by electrical stimulation, but did not effect CGRP-induced dural dilation. 6. The N-type voltage-dependent calcium channel blocker ω-conotoxin-GVIA (20 μg kg(−1), n=8 and 40 μg kg(−1), n=7) significantly attenuated the dilation brought about by electrical stimulation, but did not effect CGRP-induced dural dilation. 7. It is thought that the P/Q-, N- and L-type calcium channels all exist presynaptically on trigeminovascular neurons, and blockade of these channels prevents CGRP release, and, therefore, dural blood vessel dilation. These data suggest that the P/Q-, N- and L-type calcium channels may be involved in trigeminovascular nociception.